Perilaku Geoteknis Tanah Lanau yang Distabilisasi dengan Serutan Karet Ban - Utama, K.A.; Harianto, T.; Dwianto, D. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Recently, developments in the geotechnical-environmental engineering field have become more attractive. One of the interesting efforts to be researched is how the geotechnical behavior of silty soil reinforced with fiber from shredded tires. This study aims to evaluate silty soil's mechanical properties, which are stabilized with shredded tires. This research involved shredded tire from used tire shreds with proportions of 2%, 3%, 4%, and 5% by dry weight of soil sample. The tests of soil physical properties and mechanical properties were conducted to evaluate the characteristics of the mixture soil. The unconfined compressive strength (UCS), shear strength, California Bearing Ratio (CBR) and cracking behavior were verified to evaluate the behavior of the silty soil–shredded tires mixture. The results showed that adding 2% shredded tires performed satisfied on some of the mechanical properties tested. These results illustrate the potential of utilizing shredded tires waste as an alternative material that can reduce tire rubber waste.